In Vivo Confocal Scanning Laser Microscopy - Stachs, Oliver; Guthoff, Rudolf F.; Aumann, Silke (Springer International Publishing, 2019)
Over the past two decades, the applications of in vivo confocal laser scanning microscopy for investigating the anterior segment in the living eye have been greatly extended. Different modalities of confocal microscopy enable detailed investigation of the central and peripheral cornea, tarsal and palpebral conjunctiva, and lids, and this allows for tissue characterization at the cellular level. High-resolution imaging has established a new understanding of the functions of the ocular surface system. Confocal microscopy provides a link between conventional ex vivo histology and in vivo studies of ocular pathology, not only in clinical science but also in ophthalmological practice. Furthermore, the technique has the potential to provide reliable early biomarkers for neurodegenerative changes.